Universal parent-focused child sexual abuse prevention: A quasi-experimental protocol. - Ella Abourjaily; Kate Guastaferro; Kassidy McElwee; Christian M Connell (PLoS ONE)
Background Child sexual abuse (CSA) is a significant public health concern, and there is a lack of universal, evidence-based primary prevention interventions that extend beyond a focus solely on children. Parents remain a consistently underutilized target for primary prevention efforts aimed at mitigating CSA despite their unique relationship and close proximity to their children. CSA risk is not confined to any specific demographic, and its effects on affected children are well-documented, significantly impacting numerous dimensions of their wellbeing. Thus, there is a clear and urgent need to address this gap in prevention strategies. Methods This study will use a quasi-experimental design (target N = 412) to examine potential gains in CSA-related awareness and intentions to use protective behaviors among parents who participate in a universal parent-focused CSA prevention workshop, Smarter Parents. Safer Kids., compared to those who do not. Participants in both the control (n = 206) and experimental group (n = 206) will complete 3 survey assessments: Survey 0 (baseline), Survey 1 (1-month), and Survey 2 (3-month follow-up). The experimental group will participate in a Smarter Parents. Safer Kids. workshop between the Surveys 0 and 1. We will use data collected from the baseline to measure potential mediators of CSA-related awareness and intention to use protective and preventive behaviors. In adjacent efforts to enhance the curriculum's reach with future dissemination and implementation, we will also explore the impact of recruitment materials and strategies on parental engagement. Conclusion Results of this study will advance efforts to implement parent-focused CSA prevention with a universal audience.